Toxigenic profile and AFLP variability of Alternaria alternata and Alternaria infectoria occurring on wheat - Oviedo, Maria Silvina (2013)
Abstract The objectives of this study were to evaluate the ability to produce alternariol (AOH), alternariol monomethyl ether (AME) and tenuazonic acid (TA) by A. alternata and A. infectoria strains recovered from wheat kernels obtained from one of the main production area in Argentina; to confirm using AFLPs molecular markers the identity of the isolates up to species level, and to evaluate the intra and inter-specific genetic diversity of these two Alternaria species. Among all the Alternaria strains tested (254), 84% of them were able to produce mycotoxins. The most frequent profile of toxin production found was the co-production of AOH and AME in both species tested. TA was only produced by strains of A. alternata. Amplified fragment polymorphism (AFLPs) analysis was applied to a set of 89 isolates of Alternaria spp (40 were A. infectoria and 49 were A. alternata) in order to confirm the morphological identification. The results showed that AFLPs are powerful diagnostic tool for differentiating between A. alternata and A. infectoria. Indeed, in the current study the outgroup strains, A. tenuissima was consistently classified. Characteristic polymorphic bands separated these two species regardless of the primer combination used. Related to intraspecific variability, A. alternata and A. infectoria isolates evaluated seemed to form and homogeneous group with a high degree of similarity among the isolates within each species. However, there was more scoreable polymorphism within A. alternata than within A. infectoria isolates. There was a concordance between morphological identification and separation up to species level using molecular markers. Clear polymorphism both within and between species showed that AFLP can be used to asses genetic variation in A. alternata and A. infectoria. The most important finding of the present study was the report on AOH and AME production by A. infectoria strains isolated from wheat kernels in Argentina on a semisynthetic media for the first time. Also, specific bands for A. alternata and A. infectoria have been identified; these may be useful for the design of specific PCR primers in order to differentiate these species and to detect them in cereals.